As múltiplas redes do Programa Cultura Viva - Frederico Augusto Barbosa da Silva; Valéria Labrea (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The construction of public policies is a concrete social process that mobilizes actors and ideas. The Programa Arte Cultura e Cidadania - Cultura Viva mobilizes a significant number of actors. The main idea under discussion is that the program works on a network. The following text discusses the conceptual agreements and disagreements on the concept of network within the program in the context of Grupo de Trabalho Cultura Viva and in the context of public policy analysis.
Keywords: Z18; 330; public policy analysis; public policy network; programa Cultura Viva